2018
DOI: 10.2339/politeknik.417760
|View full text |Cite
|
Sign up to set email alerts
|

PV/T Tabanlı Bir Sistemde MATLAB/Simulink Kullanılarak Yapılan Performans Analizi

Abstract: Bu çalışmada, fotovoltaik/termal (PV/T) kolektörlerin elektriksel ve termal verim analizi yapılmıştır. Bu amaçla, sıcak su karşılama ve elektrik enerjisi üretimi için uygun olan Sıvı Tip Düz PV/T Kolektör sistemi tercih edilmiştir. Bu tip sistemlerin maksimum verimle çalışabilmesi için sızdırmazlık faktörü, ışınım, giriş sıcaklığı, ortam sıcaklığı, emici plaka parametreleri (tüp aralığı, boru çapı, kanatçık kalınlığı vb.), emici plakadaki akışkanın termal iletkenliği gibi çeşitli parametreler göz önünde bulund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The results should be evaluated and compared with other regions of the country in the light of this information. In studies conducted for Balıkesir [27], Tekirdağ [28], Manisa [29], Şanlıurfa [30], and Batman [31] provinces, the approximate electrical efficiency of PV panels was 12%, 15%, 13.5%, 6.5-7% and 13.65%, respectively while the yields of monocrystalline and polycrystalline panels, in this study conducted in Sinop, were found to be as 16.2% and 13.9%, respectively.…”
Section: Resultsmentioning
confidence: 47%
“…The results should be evaluated and compared with other regions of the country in the light of this information. In studies conducted for Balıkesir [27], Tekirdağ [28], Manisa [29], Şanlıurfa [30], and Batman [31] provinces, the approximate electrical efficiency of PV panels was 12%, 15%, 13.5%, 6.5-7% and 13.65%, respectively while the yields of monocrystalline and polycrystalline panels, in this study conducted in Sinop, were found to be as 16.2% and 13.9%, respectively.…”
Section: Resultsmentioning
confidence: 47%
“…Some studies have explored the influence of inlet water temperature on cooling effect, as it determines the heat transfer effect between the water and solar cells. When inlet water temperature is low, the temperature difference between water and solar cells is high, leading to more heat removable from PV modules and better cooling effect [60,61]. Zhang et al [49] have revealed that when decreasing the inlet temperature from 35°C to 15°C, cell temperature could be lowered by up to 9°C.…”
Section: Design Related Factorsmentioning
confidence: 99%
“…Later, in 1976, a water-type PV/T study was performed by Martin Wolf [7]. After these pioneering studies, great quanta of studies on PV/T applications have increasingly been performed [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%